Deceptive Communication: Direct Lies vs. Ignorance, Partial-Truth and Silence - Despoina Alempaki; Valeria Burdea; Daniel Read (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
In cases of conflict of interest, people can lie directly or evade the truth. We analyse this situation theoretically and test the key behavioural predictions in a novel sender-receiver game. We find senders prefer to deceive through evasion rather than direct lying, more so when evasion is a partial-truth. This is because they do not want to deceive others nor be seen as deceptive. Receivers are sensitive to the deceptive language and more likely to act in senders' favour when these lie directly. Our findings suggest dishonesty is more prevalent and costlier than previous best estimates focusing on direct lies.
Keywords: C91; D82; D91; 330